HN2O2− as a Ligand in Mononuclear Hydrogenhyponitrite‐κ2‐N, O Ruthenium Complexes with Bisphosphane Co‐Ligands. Issue 60 (18th October 2018) - Beck, Daniel; Klüfers, Peter
Abstract: The hyponitrite anion is a tentative intermediate in the reduction of nitric oxide (NO) to nitrous oxide (N2 O) catalyzed by nitric‐oxide reductase (NOR) in the process of bacterial denitrification. Owing to the considerable number of known coordination modes for the hyponitrito ligand, its actual bonding form in the enzymatic cycle is a point of current discussion. Here, we contribute to the hardly known ligand properties of a key intermediate, the monoprotonated hyponitrite anion. Three air‐ and water‐stable ruthenium complexes with hydrogenhyponitrite as the ligand were synthesized by using commercially available bisphosphane co‐ligands (1, 2‐bis(diphenylphosphino)ethane (dppe), 1, 3‐bis(diphenylphosphino)propane (dppp), 1, 2‐bis(diphenylphosphino)ethene (dppv)). The starting compounds [Ru(dppe)2 (tos)]BF4 (1 ) and [Ru(dppp)2 (tos)]BF4 (2 ) contained the bidentate coordinating tosylate anion (tos) as a particularly well‐suited leaving group. To confirm the protonated and deprotonated species, X‐ray diffraction, IR, UV/Vis spectroscopy (solution and solid state), solid‐state NMR spectroscopy, and high‐resolution mass spectroscopy were used. DFT calculations give insight into the bonding situation. We report on [Ru(dppe)2 (HN2 O2 )]BF4 (5 ), [Ru(dppp)2 (HN2 O2 )]BF4 (6 ), [Ru(dppv)2 (HN2 O2 )]BF4 (7 ), [Ru(dppp)2 (HN2 O2 )]BF4 ⋅ Imi (9 ; Imi=imidazole) as the first mononuclear trans ‐hydrogenhyponitrite complexes. Isolated deprotonated analogs are [Ru(dppe)2 (N2 O2 )]⋅ HImi(BF4 ) (8 ) and [Ru(dppv)2 (N2 O2 )]⋅ HImi(BF4 )⋅ Imi (10 ). Abstract : The trans ‐hydrogenhyponitrito ligand, a tentative intermediate in the biological NO‐to‐N2 O transformation, was stabilized in some mononuclear ruthenium(II) chelates. Depending on the chosen co‐ligand, the weak base imidazole did not (as shown in the figure) or did deprotonate this ligand.